The effects of breadfruit leaf (Artocarpus Altilis) extract on fibroblast proliferation in the tooth extraction sockets of Wistar rat - Darin Hulwani Rinaldi; David B. Kamadjaja; Ni Putu Mira Sumarta (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: A prolonged tooth extraction socket healing process can affect the well-being of the patient and increase the risk of infection. Fibroblast proliferation in the proliferation phase is an important stage in the healing process. Fibroblast formed from extracellular matrix and collagen fibers support bone formation in the socket. Breadfruit leaves, extremely common in Indonesia, contain polyphenol, flavonoid, tannin and alkaloid substances which accelerate the wound healing process because of their anti-inflammatory, anti-bacterial and anti-oxidant properties. A previous study showed that 16% breadfruit leaf gel extract administered to Wistar rats produced an encouraging anti-inflammatory effect, but its capacity for increasing fibroblast proliferation remains to be fully understood. Purpose: The aim of this study was to observe the effect of applying breadfruit leaf extract on fibroblast proliferation on the healing process in tooth extraction sockets. A preliminary phytochemical study was undertaken. Methods: 24 Wistar rats were divided into four groups: two control groups and two experimental groups. 16% breadfruit leaf gel extract was applied to the experimental groups, while none was applied to the control groups. The number of fibroblasts was counted on both the third and fifth days post-extraction. Data was analyzed statistically using an independent T-test. Results: There were significant differences in the number of post-extraction fibroblasts in Wistar rat tooth sockets on day 3 (p=0.000; p < α=0.05) and day 5 (p=0.000; p < α=0.05). Conclusion: Breadfruit leaf gel extract application increases fibroblast proliferation during the healing process in the tooth extraction sockets of Wistar rats.